Lost Bones: The Archaeology of Rice Lake - Snyder, Alex (My University, 2011)
This paper summarizes the history of two major Indian burial mound groups in the City of Rice Lake in Barron County, Wisconsin. These mound groups are: The Rice Lake Mound Group, of which a few remaining mounds are preserved within a city park, and the Cyrus Thomas Mound Group, remnants of which lay across the lake to the northeast in the Hiawatha Park area. The archaeological culture responsible for the city's mounds is also discussed. Finally, this paper examines recent regulatory changes to the Native American Graves Protection and Repatriation Act of 1990 and the impact these changes may have on human remain and artifact collections from Rice Lake. The author finds that the history Rice Lake's mounds has been--and continues to be--a microcosm of an important part of United States history.
Keywords: Rice Lake (Wis.)--Antiquities; Barron County (Wis.)--Antiquities; Mounds--Wisconsin--Barron County; Mounds--Wisconsin--Rice Lake; Rice Lake Mound Group (Wis.); Cyrus Thomas Mound Group (Wis.); Indians of North America--Wisconsin--Antiquities